2022
DOI: 10.1007/s40692-021-00218-4
|View full text |Cite
|
Sign up to set email alerts
|

E-learning bibliometric analysis from 2015 to 2020

Abstract: This study aims to comprehensively examine the e-learning research field by conducting a bibliometric analysis of 12,272 publications between 2015 and 2020 from the WoS database. The study aims to highlight collaborations between authors, universities, and countries in the field, to identify the most influential authors, universities, countries, and reference papers; to know the research topics on which researchers have been working in recent years, and to examine African contribution in the field. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 19 publications
5
45
2
Order By: Relevance
“…The publication trend is experimenting with a light decrease, which could be explained by the decline in the publication in a specific area such as Engineering or the shift to experimental analysis. These results match those of Dégila et al [ 61 ], which identified a decrease in e-learning in education publications and indicated how this decrease could be partially motivated by the COVID-19 pandemic. Nonetheless, the precious bibliometric analysis has not fully presented a possible reason for this research area’s decline.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The publication trend is experimenting with a light decrease, which could be explained by the decline in the publication in a specific area such as Engineering or the shift to experimental analysis. These results match those of Dégila et al [ 61 ], which identified a decrease in e-learning in education publications and indicated how this decrease could be partially motivated by the COVID-19 pandemic. Nonetheless, the precious bibliometric analysis has not fully presented a possible reason for this research area’s decline.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, these findings are in sync with previous bibliometric articles in the educational field that indicated a high presence of European countries, especially Spain [ 45 , 61 ]. The initial relevance of European countries could be linked to the UNESCO initiatives from the Decade of Education for Sustainable Development and the fourth goal of sustainable development goals of the agenda 2030, which was related to leading [ 23 , 54 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Students feel the essence of physical classes in these virtual meetings or online courses (Kumar Basak et al, 2018). Obviously, Smart Learning or IoT based E-Learning effects enhance the students' performance in terms of achievement, knowledge, learning, and results (Saiyeda, 2021;Djeki et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is the use of mathematical and statistical approaches to assess the academic publication research output in a specific domain [17]. Only a few bibliometric studies have looked into and evaluated research efforts on e-learning in general [18][19] [20][13] while other performed the similar analysis on the concept of m-learning [21][22] [23][24] [25]. Digital learning is still a new concept that has piqued the interest of academicians.…”
mentioning
confidence: 99%